Another possible modernity. The baroque ethos in the thought of Bolívar Echeverría - Giraud Billoud, Michel (2025)
This article seeks to analyze the philosophical approach made by the Ecuadorian thinker Bolívar Echeverría to the concept of baroque ethos. To achieve this goal, it begins by considering two issues that Echeverría has worked on during his theoretical development: the illusions of European modernity and the inherent contradictions of capitalism. Both devices have shaped Western history in recent centuries. Faced with capitalism, as a fact, Echeverría’s philosophical proposal is aimed at thinking about different ethos as ways of understanding and assuming this capitalist fact. Where the baroque ethos acquires relevance because unlike the other ethos, it opts for a different path of transforming the contradictions of capitalism into a possibility of building a horizon based on the principle of life.